Analysis of Pulmonary Tuberculosis based on Home Sanitation in Sembung Hamlet, Margopatut East Java - Ema Mayasari; Dyah Risnasari; Nway Eint Chei (STRADA : Jurnal Ilmiah Kesehatan, 2022)
Pulmonary Tuberculosis (TB) disease is a contagious disease. TB can spread quickly in environment with sanitation. The study aimed to analyze the effect of house sanitation toward pulmonary TB incidence in Sembung Hamlet, Margopatut Village, Sawahan District, Nganjuk Regency. The study is quantitative analytic research with a cross sectional approach. The study was conducted toward 212 respondents taken using simple random sampling. The results showed that there was an influence of house sanitation including house ventilation, type of floor, sky, the ceiling of the house, lighting, and residential density of houses toward pulmonary TB incidence in Sembung Hamlet, Margopatut Village, Sawahan District, Nganjuk Regency. People who have house with high density occupancy should rearrange the number occupants and can consider seeking other room with more spacious space. People need arrange the house or room so the room can get better air circulation and natural lighting to the house or room.